ANALISIS PROSES TERCIPTANYA GOL DALAM CABANG OLAHRAGA SEPAK BOLA PUTRI PADA OLYMPICS GAMES TAHUN 2024 DI KOTA PARIS PRANCIS - Riera Faizah Destriaf; Widodo, Achmad; Fithroni, Hijrin; Dzul Fikri, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine how goals are created in the women's football branch of the 2024 Olympic Games in Paris through video analysis with an observational descriptive approach. All goals are analyzed thoroughly by reviewing the type of attack, the tactical context, the location of the opportunity, and the form of the final finish. Data is collected from full match footage, highlight footage and official statistics, and then processed descriptively to map out the attack patterns and zones that contribute the most to the goal. The results of the analysis showed that open play was the main source of goals with a percentage of 67.10%, followed by set-piece situations such as free kicks (13.16%) and corner kicks (9.21%). In terms of finalization areas, the penalty box (area 17) emerged as the most decisive zone with a contribution of 76.31%, while area 14 outside the penalty box accounted for 22.37%. These findings confirm that effective open attacks including neat build-ups, dynamic player movements, and space utilization in the final third area are dominant factors in goal creation. The results of this study are expected to be a reference for coaches and analysts in developing offensive strategies and training programs that are more in line with the characteristics of the modern women's football game.